Religious Board Design: An Augmented Reality-Based Interactive Learning Media Prototype for Enhancing Religious Literacy in Islamic Education - Tanwir M.Y.M Raif; Mohammad Zakki Azani (FKIP - Universitas Riau, 2026)
Islamic Religious Education (PAI), particularly Islamic History (Tarikh Islam), is often delivered through textual and teacher-centered approaches that may limit student engagement and religious literacy development. This study aims to design and develop an interactive learning media prototype, namely the RELIGI BOARD, which integrates gamification and Augmented Reality (AR) to support Islamic History learning at the junior high school level. The research employed a Research and Development approach, adopting the first three stages of the ADDIE model: Analysis, Design, and Development. Data were collected through needs analysis interviews with teachers and analyzed using qualitative descriptive methods to examine the design feasibility and theoretical foundation of the media. The results indicate that the RELIGI BOARD prototype is functionally and structurally feasible as an interactive learning medium. The integration of board game mechanics with AR-based visualizations supports the presentation of abstract historical concepts in a more concrete and engaging form. From a theoretical perspective, the convergence of gamification principles and AR technology offers a potential solution to motivational and cognitive challenges in Islamic History learning. Although limited to the prototype development stage, this study suggests that the RELIGI BOARD has potential as an innovative learning media to support religious literacy in Islamic Education.